2017
DOI: 10.1002/chem.201701354
|View full text |Cite
|
Sign up to set email alerts
|

Stable NiII Porphyrin meso‐Oxy Radical with a Quartet Ground State

Abstract: 10,15,20-Tris(pentafluorophenyl)-substituted Ni -porphyrin meso-oxy radical bearing two coordinating pyridines was synthesized as a stable radical with a quartet ground state (S=3/2). X-ray structural analysis revealed that the Ni porphyrin moiety is fairly planar and the Ni-N bond lengths are considerably longer, indicating the high-spin state of the Ni center. The radical exhibited a quartet ground state, indicating the ferromagnetic interaction between the high-spin Ni center (S=1) and the porphyrin meso-ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The negative charge of the deprotonated species can be delocalized on the π-electronic unit for stabilization. Ni II porphyrin NiOH , which has a hydroxy unit at one of the meso positions (Sasano et al., 2017, Stähler et al., 2017), was used as the precursor for the π-electronic anionic species NiO – as the counteranion for the porphyrin–Au III cation (Figure 10) (Stähler et al., 2017). The countercation of NiO – was exchanged using the following stepwise preparation protocol: (1) NiOH in CH 2 Cl 2 was treated with an excess amount of aqueous NaOH to yield Na + - NiO – in a CH 2 Cl 2 phase and (2) after washing with water to remove NaCl and subsequent recrystallization with EtOAc/ n -hexane, 1 equiv.…”
Section: Resultsmentioning
confidence: 99%
“…The negative charge of the deprotonated species can be delocalized on the π-electronic unit for stabilization. Ni II porphyrin NiOH , which has a hydroxy unit at one of the meso positions (Sasano et al., 2017, Stähler et al., 2017), was used as the precursor for the π-electronic anionic species NiO – as the counteranion for the porphyrin–Au III cation (Figure 10) (Stähler et al., 2017). The countercation of NiO – was exchanged using the following stepwise preparation protocol: (1) NiOH in CH 2 Cl 2 was treated with an excess amount of aqueous NaOH to yield Na + - NiO – in a CH 2 Cl 2 phase and (2) after washing with water to remove NaCl and subsequent recrystallization with EtOAc/ n -hexane, 1 equiv.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Osuka et al reported a strong ferromagnetic interaction in the meso -pentafluorophenylporphyrin Ni( ii ) complex 78Ni . 66 The authors suggested that the balance of magnetic interactions between the central metal and the ligand radical was likely to be sensitive, so that a very small structural distortion could alter the magnetic interaction.…”
Section: Non-innocent Macrocyclic Radicalsmentioning
confidence: 99%
“…In recent years, it has been demonstrated that porphyrinoids have a superior ability to stabilize their conjugated radicals due mainly to their extensive spin delocalization. This remarkable ability has allowed the exploration of various stable radicals including porphyrinoid meso ‐oxy radicals, [3a–i] porphyrinoid meso ‐aminyl radicals, [3j–o] and porphyrin meso ‐carbon radicals [3p–r] . Wu et al.…”
Section: Figurementioning
confidence: 99%